Analysis of Sports Facility Service Quality on Goro Consumer Satisfaction Arena Makassar - Muhammad Hanif Muhtadi; Ramli Ramli; Herman Herman; Muh. Adnan Hudain; Irvan Irvan (UNIVERSITAS NEGERI MAKASSAR, 2024)
This research is a quantitative descriptive study that aims to clarify customer satisfaction at Goro Arena. The population in this study was 145 members registered at Goro Arena. Sampling technique with the accidental sampling method. The sample was 22 members who were doing sports activities at the Goro Arena. The instrument used to understand customer satisfaction is a questionnaire. The data analysis technique uses using quantitative descriptive analysis method with percentages. Based on the research analysis, the quality of sports facility services on customer satisfaction at the Makassar Goro Arena is very satisfactory with a percentage of 57%. According to Parasuraman in Jayanti (2016), the form of service quality application uses the concept of